Influence of indigenous arbuscular mycorrhizal fungus and bacterial bioinoculants on growth and yield of Capsicum chinense cultivated in non-sterilized soil. (10th April 2019) - Surendirakumar, K.; Pandey, R. R.; Muthukumar, T.
Abstract: Despite the global importance of Capsicum species, there is limited information on the indigenous endomycorrhizal fungal association in this crop. Therefore, the diversity and colonization patterns of arbuscular mycorrhizal fungi (AMF) in roots of Naga King chilli ( Capsicum chinense ) were assessed during pre-flowering, flowering and fruit ripening growth stages under a sub-tropical shifting cultivation system of North Eastern India. All the roots examined had AMF colonization and the presence of Paris -type arbuscular mycorrhizal morphology is reported for the first time in C. chinense . A total of 11 AMF spore morphotypes were isolated from both field and trap culture soils. Maximum AMF spore density and root colonization were recorded during the pre-flowering and flowering stages, respectively. The influence of Funneliformis geosporum, individually or in combination with Pseudomonas fluorescens and Azotobacter chroococcum, on growth and yield of C. chinense, was evaluated in a pot experiment using sterilized and non-sterilized soils. The application of AMF and P. fluorescens to sterilized soil significantly increased the growth, flower and fruit production, and nutrient content of C. chinense . The highest growth rates and yields of C. chinense in non-sterilized soils were achieved when AMF was combined with both P. fluorescens and A. chroococcum . The results of the current study indicate the value of applying microorganisms to improve plant growth and performance in chillies. One of the mechanisms for this could be the facilitated assimilation of nutrients promoted by AMF and bacterial bioinoculants.